2022
DOI: 10.1177/10464964221117483
|View full text |Cite
|
Sign up to set email alerts
|

How Are We Similar? Group Level Entitativity in Work and Social Groups

Abstract: Entitativity is essential for individuals to experience a grouping of people as a “group.” However, entitativity is primarily studied at the individual level. If it is truly a fundamental component of group outcomes and processes, it should be considered a group-level construct. We establish that group members can share entitativity perceptions. We propose that entitativity develops in work and social groups through different self-categorization processes. Social groups can take advantage of top-down processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Thus, future research should empirically test the relative impact of each CCP component on the different outcomes and what patterns of the integration of cultures exist across units. Relatedly, Blanchard et al (2022) have recently shown the variability that is explained by entitativity, a similarly higher-level phenomenon. Furthermore, there may be a potential need for further training to integrate other cultures when the composition of the unit changes.…”
Section: Future Researchmentioning
confidence: 93%
“…Thus, future research should empirically test the relative impact of each CCP component on the different outcomes and what patterns of the integration of cultures exist across units. Relatedly, Blanchard et al (2022) have recently shown the variability that is explained by entitativity, a similarly higher-level phenomenon. Furthermore, there may be a potential need for further training to integrate other cultures when the composition of the unit changes.…”
Section: Future Researchmentioning
confidence: 93%
“…The parameters used in the sensitivity power analyses can be found on the OSF page. We conducted a sensitivity power analysis using the pwr2ppl package in R (Aberson, 2022; R Core Team, 2023), finding at least 80% power to detect an indirect effect based on correlations between study variables that are comparable to previous research and the theoretical relationship between the variables (Blanchard et al, 2022; Effron & Knowles, 2015; Hogg et al, 2012; Kunst & Obaidi, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…First, this work integrates research on leader prototypicality (e.g., Haslam et al, 2020; Hogg, 2001; Hogg et al, 2012; Steffens et al, 2021) and group entitativity (e.g., Campbell, 1958; Lickel et al, 2000). Despite being theoretically related (e.g., Blanchard et al, 2022), to the authors’ knowledge there is no published research examining whether perceptions of leader prototypicality bolster perceptions of group entitativity. By observing that leader prototypicality positively predicts perceived political group entitativity, we could fully (Study 1) or partially (Study 2) explain the relationship between perceived political leader prototypicality and willingness to violently defend the in-group from political rivals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation